ANALISIS KARAKTERISTIK KUALITATIF DALAM PENYAJIAN DAN PENGUNGKAPAN LAPORAN KEUANGAN BERDASARKAN IASB DAN DSAK IAI - Winny Oktariska Zega; Karen Soli Gracia Ndruru; Hamonangan Siallagan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The characteristics of financial statements are the primary foundation for building stakeholder trust in making economic decisions. This study aims to highlight and compare the qualitative characteristics of financial statement presentation and disclosure with the standards of the International Accounting Standards Board (IASB) and the Financial Accounting Standards Board of the Indonesian Institute of Accountants (DSAK IAI). This study uses a qualitative descriptive method with a comparative study approach, analyzing and assessing the application of international accounting standards to domestic regulations in Indonesia. The study results indicate that DSAK IAI successfully harmonizes the Fundamental Characteristics and Supporting Characteristics in accordance with IASB guidelines. However, the inclusion of elements in the representation remains a significant obstacle due to management subjectivity, which is still oriented towards legal formalities rather than economic substance. This study concludes that the successful presentation of relevant financial information lies in the synergistic harmonization of regulations and compliance with financial statement preparation.